Legal and Ethical Responsibilities of Geoscientists in Environmental Geology - Reichelt, Raymond (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2014)
Professional geoscientists, including those practicing environmental geoscience, have definite and definable legal and ethical responsibilities. These obligations apply to environmental geoscientists working as consultants, academics, regulators or environmental managers. Environmental geoscientists are obliged to be aware of and obey all federal, provincial and municipal laws and regulations applying to professional geoscientists. As well as the provincial engineering and geoscience acts, a variety of additional guidelines and professional standards apply to the professional geoscientist. These include criminal, labour, and business law as well as environmental acts and regulations. Governments, professional associations and private standards agencies, such as the Canadian Standards Association and the American Society for Testing and Materials, have also issued relevant guidelines and standards.